Optimalisasi Dampak Pembangunan Pariwisata Terhadap Masyarakat Lokal; Studi Di Desa Lalos Kecamatan Galang Kabupaten Tolitoli - Sawir, Mohammad; Lestari, Ayu (LPPM Universitas Madako Tolitoli, 2025)
Lalos Village is one of the tourist villages prioritised for tourism development due to its significant potential to be developed into a leading tourist destination in Tolitoli Regency. This study aims to analyse the strategies the local government should implement to optimise the benefits of tourism development for local communities, particularly in emerging tourist villages like Lalos Village. The research data were analysed using a qualitative approach. Literature studies and semi-structured interviews were conducted with informants selected purposively to represent various stakeholder groups. The findings emphasise the importance of solid cooperation between the local government, village government, business actors, and local communities. This cooperation is realised through the active involvement of all parties to accommodate their respective interests, ensuring that the goals of sustainable tourism development can be achieved in Lalos Village, a tourist village located in a frontier area. As the policy maker and primary driver of tourism development, the local government should involve the local community in every development activity according to their needs. The local community should not merely be positioned as objects but also as subjects of tourism development to minimise the negative impacts. The strategic steps needed to optimise the benefits of tourism development for the local community include: (1) Establishing dialogues among stakeholder groups, (2) Comprehensively identifying the needs of the local community, (3) Utilising existing resources and social media platforms, and (4) Building a collective commitment to ensure the implementation of strategies.